Effect Of Chicken Egg Cell As A Mixture Of Plant Media On The Growth Of Number Of Leaf Long Beans (Vigna Unguiculata L.) - Safira Mustaqilla; Muhibbuddin Muhibbuddin; Hafnati Rahmatan; Wardiah Wardiah; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Eggshell waste is only considered as household waste, even though eggshell waste can be used as a planting medium. Therefore, it is necessary to use chicken egg shells so that they do not become waste and as a source of mikro elements for soil fertility and maintaining soil pH for the growtth of long bean. To determine the effects of planting media mixed chicken egg shells on the growtth of longs beans (Vigna unguiculata L.). The approach use in this research is quantiitative, the type of researches used is an experimentals use a completely randomized design (CRD). The parameter observed was the fresh fruit weight (g). Data was analyze use Analysis of Variance (ANAVA). The results showed that there was a significants effects (F count ≥ F table 0.05) on the administration of chicken egg shells as a mixture of planting media on the growth of long bean plants and the highest treatment was obtained in treatment P7 (70 g of chicken egg shell growing media) while the smallest amount obtained in treatment P0 (control). The result of this study is that the addited of chicken egg shells as a mixture of planting media has a significant effect on increasing the growth of long bean plants.Keywords: growing media, eggshell, long bean, growth Cangkang telur dianggap sebagai limbah rumah tangga, padahal limbah cangkang telur bisa digunakan sebagai sarana media tanam. Oleh karena itu, perlu dimanfaatkan cangkang telur ayam agar tidak menjadi limbah dan sebagai sumber unsur mikro untuk kesuburan tanah dan menjaga pH tanah untuk pertumbuhan kacang panjang. untuk mengetahui pengaruh media tanam campuran cangkang telur ayam terhadap pertumbuhan kacang panjang (Vigna unguiculata L.). Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif, jenis penelitian yang digunakan adalah eksperimen yang menggunakan Rancangan Acak Lengkap (RAL). Parameter yang diamati adalah berat basah buah (g). Data dianalisis menggunakan Analisis Varian. Hasil penelitian menunjukan bahwa terdapat pengaruh nyata (F hitung ≥ F tabel 0,05) pada pemberian cangkang telur ayam sebagai campuran media tanam terhadap pertumbuhan tanaman kacang panjang dan perlakuan tertinggi diperoleh pada perlakuan P7 (70 g media tanam cangkang telur ayam) sedangkan jumlah terkecil diperoleh pada perlakuan P0 (kontrol). Simpulan dari penelitian ini adalah pemberian cangkang telur ayam sebagai campuran media tanam berpengaruh nyata dalam meningkatkan pertumbuhan tanaman kacang panjang.Kata kunci: media tanam, cangkang telur, kacang panjang, pertumbuhan